ANALYSIS OF DOMINANT RISK FACTORS FOR HYPERTENSIVE DISEASE: Analisis Faktor Risiko Dominan terhadap Penyakit Hipertensi (Data Sekunder Puskesmas Kecamatan Johar Baru, Jakarta Pusat Tahun 2021) - Johannes Bastira Ginting; Tri Suci (Universitas Airlangga, 2023)
Background: Hypertension is a non-communicable disease with a high morbidity and mortality rate. This disease frequently triggers the iceberg phenomenon as numerous individuals remain unaware of the affliction. Aim: This study determines the most dominant risk factors for the incidence of hypertension. Methods: The quantitative study method used was conducted in September 2022. The study population utilized secondary data sourced from the Visit data at the Johar Baru Health Center in South Jakarta during 2021. The initial dataset consisted of 102,647 patients, out of which 13,946 had hypertension. Furthermore, data analysis involved employing the Chi-square test and Multiple Logistic Regression, with a significance level of 95%. Results: The Chi-Square test yielded significant results, indicating a relationship between risk factors for hypertension and seven out of the nine free variables examined. These variables included Body Mass Index (BMI) (p-value=0.000), excess salt consumption (p-value=0.000), underfeeding fruits and vegetables (p-value=.000), lack of physical activity (p-value=0.000), excess fat consumption (p-value=0.000), gender (p-value=0.000), and age (p-value=0.000), with a p-value of <0.05. Meanwhile, smoking (p-value=0.516) and drinking alcohol (p-value=0.859) variables, with a p-value of >0.05 had no relationship. Conclusion: The result showed that BMI was the most dominant risk factors for hypertension, with an OR of 1,610. Therefore, people with an abnormal BMI have a 1,610 times risk of developing hypertension.